Penerapan Model Network Development Life Cycle (NDLC) Pada Infrastruktur Jaringan Internet Kantor Desa Kemiri - Miftahur Rahman; Ravi Budi Handwika; Ahadini Izzatus Zahro (Lembaga Pengembangan Kinerja Dosen, 2023)
The growth of world internet users and especially in Indonesia continues to increase along with the development of information and communication technology. So that with the internet or wifi network helping human work it can be easier to get information in a relatively short time and with better results, such as the Kemiri Village Office which serves its citizens every day in managing administration. The problem that occurs in the Kemiri Village Office, Panti District, Jember Regency is the unavailability of internet or wifi services, resulting in slow service to residents when managing administration, especially those related to having to access the distribution information system, so Kemiri Village requires an internet or wifi network. This research is in its development using the network development life cycle (NDLC) model. Producing research, namely the establishment of an internet network infrastructure for the Kemiri Village Office, thus facilitating the daily work of village officials in serving residents or their communities in managing administration.